Students’ Anxiety Levels in TOEFL Testing at STKIP Muhammadiyah Aceh Barat Daya - Fiha Aynun Jariah; Nuzulul Isna (STMIK Indonesia Banda Aceh, 2025)
This study investigates the anxiety levels of students at STKIP Muhammadiyah Aceh Barat Daya when taking the TOEFL (Test of English as a Foreign Language) as one of the graduation requirements. Using a descriptive quantitative research design, data were collected from 70 English Education students 6 male and 64 female—who had taken the TOEFL but had not yet reached the passing score of 485 for the paper-based test. The Test Anxiety Questionnaire by Nist and Diehl, adapted by Muliawati et al. (2020), was used to measure cognitive, physical, and emotional aspects of anxiety. The results showed that the majority of students (77.1%) experienced moderate anxiety, followed by 18.6% with mild anxiety, and 4.3% with severe anxiety. Cognitive anxiety emerged as the most affected aspect, with difficulty choosing an answer being the most frequently reported symptom. These findings indicate that while anxiety is common during TOEFL testing, most students can manage it effectively. The study suggests the need for targeted strategies such as exam simulations, stress management training, and counseling services to help students optimize their performance